Will action taken under the Minamata Convention on Mercury need to be coordinated internationally? Evidence from an optimization study suggests it will. Issue 127 (January 2022) - De Simone, Francesco; D'Amore, Francesco; Hedgecock, Ian M.; Bruno, Delia Evelina; Cinnirella, Sergio; Sprovieri, Francesca; Pirrone, Nicola
Abstract: The Minamata Convention on Mercury is an international treaty with the objective of protecting human health by controlling and restricting mercury use and its release to the environment. Numerical modeling tools currently used to study the fate of mercury released to the atmosphere tend to answer questions such as 'what would be the result of a 50% decrease in mercury emissions from this region, or that emission sector?'. They are not generally designed to answer the questions of the type, 'How can a, say 25% reduction, in deposition be achieved for a particular terrestrial ecosystem/region or oceanic basin?'. This paper presents an optimization framework which exploits the numerical tractability and the real-time features of an emulator for Global Chemical Transport Mercury Models. The HERMES emulator uses the results of a large number of scenario simulations to provide the user in real-time the impact on mercury deposition resulting from changes in anthropogenic mercury emissions. The changes in emissions can be by emission sector, emission region or changes in the speciation of the emissions. The optimization framework extends the capabilities of the emulator to give the user the possibility to define a deposition reduction target in one or more regions, and the framework calculates the optimal set of emissions reductions from industrial macro-sectors considering all the geographical source regions. The user may set a maximum feasible emission reduction in each of the sectors or regions, and within these constraints the optimization framework calculates the minimum number of regions in which the emission abatement would need to be applied to achieve the target, or informs the user that the desired target is unattainable with the supplied constraints. The results from the case-study presented here not only demonstrate the need for action to implement the Convention to be concerted and coordinated internationally, but also the usefulness of an optimization framework to tailor policies for specific environmental targets. Highlights: The CTMs used to study the fate of Hg are not suited to be included in optimisation models due to their complexity. HERMES-OPT is an optimization framework that exploits the numerical features of the CTM emulator, HERMES. HERMES-OPT was used to illustrate the need for coordinated actions to be taken under the Minamata Convention on Mercury. ·Many regions must be involved in the abatement of Hg emissions to reach Hg deposition levels that are meaningful.